Adolescent Mental Health Promotion: Could it be Assisted by Considering the Functions of Depression in Young People? - Joyce, Andrew; Pauli-Myler, T.; Burns, Sharyn; Howat, Peter; Maycock, Bruce (The Clifford Beers Foundation, 2008)
Evolutionary psychopathology seeks causal explanations of mental illness consistent with theories derived from natural selection. Central to this approach is reasoning about and investigating why such high rates of mental illness occur in early adulthood, specifically during the reproductive years. Preventing mental ill-health is a fundamental aim of mental health promotion, so research programmes devoted to understanding the causality of mental illness should be of prime interest to mental health promotion practitioners and policy makers. This particular understanding of mental health highlights some of the peculiar features of our current lifestyles and environments that facilitate mental ill-health. These are factors beyond the immediate control of most settings where mental health promotion is conducted for adolescents, which could explain why such programmes have not met with much success. Current programmes targeting prevention and stigma reduction around depressionmay benefit from considering evolutionary psychopathology.